Computed Tomography Angiography Versus Digital Subtraction Angiography for Postclipping Aneurysm Obliteration Detection: A Meta-Analysis. Issue 2 (February 2019) - Uricchio, Matthew; Gupta, Saksham; Jakowenko, Nicholas; Levito, Marissa; Vu, Nguyen; Doucette, Joanne; Liew, Aaron; Papatheodorou, Stefania; Khawaja, Ayaz M.; Aglio, Linda S.; Aziz-Sultan, Mohammad Ali; Zaidi, Hasan; et al.
Abstract : Background and Purpose—: Digital subtraction angiography has been used as the gold standard to confirm successful aneurysmal obliteration after aneurysm clipping procedures using titanium or cobalt alloy clips. Computed tomographic angiography is a newer, less invasive imaging technique also used to confirm successful aneurysmal obliteration; however, its use compared with digital subtraction angiography remains controversial. Methods—: A comprehensive literature search was conducted on Pubmed, EMBASE, and Cochrane databases through November 6, 2017, for studies that evaluated postclipping aneurysm obliteration with both computed tomographic angiography and digital subtraction angiography. Pooled sensitivity, specificity, positive likelihood ratio (LR+), and negative likelihood ratio (LR−) were calculated using the bivariate random-effects model. Results—: Out of 6916 studies, 13 studies met inclusion criteria for this meta-analysis. A total of 510 patients with 613 aneurysms were included. Compared with digital subtraction angiography, which detected 87 residual aneurysms, computed tomographic angiography detected 58 resulting in a pooled sensitivity of 69% (95% CI, 54%–81%) and a pooled specificity of 99% (95% CI, 97%–99%). This corresponded to LR+ of 55.5 (95% CI, 23.6–130.9) and LR− of 0.31 (95% CI, 0.20–0.48). Univariate meta-regression revealed that the pooled sensitivity was worse in prospective designs ( P interaction <0.05), and the pooled specificity was better in higher-quality studies and for postoperative aneurysm diameters of <2 mm ( P interaction <0.001 for both). Conclusions—: This meta-analysis revealed that computed tomographic angiography had a favorable LR+ but not a favorable LR−. Thus, this imaging modality may be applicable to rule in, but not rule out, residual aneurysms after clipping. Abstract : Supplemental Digital Content is available in the text.